Исследование причин кризиса в контексте развития научных представлений о природе экономической цикличности - Черногорова, К.А. (Культура народов Причерноморья, 2013)
A major role in the crisis management and regulation is played by the strategy involving prevention of crisis phenomena in the activities of business units at various levels (national economy, region, enterprise). However, it is impossible to develop effective proactive measures that can prevent the development of unwanted situations in the future without understanding the reasons that violate the basics of stable economic activity and hamper the sustainable development. This article provides an overview of the main theories of economic cycles and theoretical conceptualization of the crisis causes at different stages of the economic science evolution. Particular attention is given to modern trends in studies of economic dynamics, in particular to the development of a modern non–classical approach. The opportunities for further development of the economic cycles and crises theory are analyzed. The study found that views on the causes of the crisis changed at every stage of history depending on the priorities, views on current events, and trends in the economic science development.